Detecção de SARS-CoV-2 em caninos e felinos através de RT-qPCR em Cuiabá, MT - Jarrah, Samar Afif (2021)
In December 2019 several people in China suffered from pneumonia of unknown origin and the common point between these individuals was the Fish Market in Wuhan City, where several wild animals were traded. Subsequently, a new Coronavirus was discovered by genetic sequencing that crossed the interspecies barriers, drastically affecting humanity in 2020, the disease became a pandemic and affected most countries in the world. This study aimed to detect the presence of the SARS-CoV-2 virus in dogs and cats for future studies of the epidemiological importance of these animals in the transmission chain. Oral, nasal, rectal and blood swabs were collected from 17 dogs and 10 cats of varying ages and breeds in homes with COVID-19 positive tutors from the Cuiabá region from May to November. Of these animals, a six-monthold feline was positive on the RT-qPCR test. 43 days after the first detection, it died due to being run over. At necropsy, strong immunomarking was observed in the respiratory epithelium of the nasal conchae, trachea, bronchi, serous cells of the tracheobronchial submucosal gland, renal epithelial cells marking contorted tubules, collecting duct and intestinal glandular epithelium. The expression of the antigen observed in the lung also showed positivity in type 1 and 2 pneumocytes and alveolar macrophages. Smooth immunostaining was observed in the bacillus macrophages and in the arterial endothelium. This work highlighted the importance of monitoring animals infected with SARS-CoV-2 and that further studies are needed to understand the pathogenesis and epidemiology of this virus in animals, aiming at One Health.